The effect of the Copenhagen Adduction and Nordic Hamstring exercises on muscle strength and athletic performance: A quasi-experimental study - Christos Pippas; Nikolaos Dagloukiaris; Antonios Antypas; Emmanouil Touloupis; George Gioftsos (Journal of Orthopaedic Reports)
Background: Two of the most common exercises used in prevention as well as rehabilitation protocols are the Nordic Hamstring (NH) and Copenhagen Adduction (CA). Although their strength effect has been investigated, the effect of the combination of both exercises on muscle strength, jump and sprint performance of male football (soccer) players has yet to be determined. Materials and methods: A total of 38 players (15.3 ± 0.49 years, 59.7 ± 7.14 kg, 152.1 ± 53.3 cm) of a Greek football club participated in a progressive 4-week strengthening program, performing both the NH and CA exercises twice a week during the team's pre-season period. Isometric hamstring and eccentric hip adduction strength were assessed using a hand-held dynamometer, while jump and sprint performance were also tested. Perceived exertion was recorded throughout the intervention. Results: Isometric hamstring strength increased by 11 % (p < 0.000) and eccentric adduction strength increased by 17 % (p < 0.000). There was a decrease of 5–7% (p = 0.000 to p = 0.034) in jump performance, and an improvement of 2–3% (p = 0.009 to p = 0.253) in sprint performance. There was no statistically significant difference for perceived exertion between the two exercises (p = 0.084–1.000). Conclusion: A 4-week progressive exercise program with the Nordic Hamstring and Copenhagen Adduction exercises combined resulted in statistically significant improvements in both isometric hamstring and eccentric adduction strength, but it did not lead to significant results in jump and sprint performance.